Income Satisfaction Inequality and its Causes - Ada Ferrer-i-Carbonell; Bernard M.S. Van Praag (Tinbergen Institute, 2002)
In this paper, the concept of Income Satisfaction Inequality is operationalized on the basis of individual responses to an Income Satisfaction question posed in the German Socio-Economic Panel (GSOEP). Income satisfaction is the subjective analogue of the objective income concept and includes objective income inequality as a special case. The paper introduces a method to decompose Income Satisfaction Inequality according to the contributions from variables such as income, education, and the number of children. Given the panel structure of the data, inequality may be attributed partly to permanent individual circumstances and partly to transitory changes. The paper shows that permanent income explains the largest part of Income Satisfaction Inequality; for non-working individuals, the age distribution is very relevant as well. Additionally, other variables such as number of adults, education, and having a partner explain most of the remaining Income Satisfaction Inequality.
Keywords: D63; I32; 330; Equivalent Income; Financial Satisfaction; Income Satisfaction; Inequality; Variance Decomposition; Welfare; Einkommensverteilung; Lebensqualität; Schätzung; Deutschland; Varianzanalyse